2020
DOI: 10.1007/s40430-020-02684-w
|View full text |Cite
|
Sign up to set email alerts
|

An effort for resolving redundancy of a multi-finger robotic hand in straight-line motions

Abstract: Multi-finger robotic hands are the main robotic invention for providing assistive movement therapy in hand rehabilitation. In this paper, the concept of task priority is adopted in order to solve the redundancy resolution of a robotic hand. The redundancy parameter has been used to design the inverse kinematic model in order to determine the joint angles when the finger moves to perform the initial subtask of tracing the desired trajectory while considering the secondary subtask of increasing the instantaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A kinematic model is developed for the proposed design in order to analyze the form of walking pattern, the working space, and the payload 21) . Kinematic Analysis helps to determine the motion capabilities of the robot along with its workspace and the area required for its operation 22) . Literature have shown that there are a number of leg types currently working for hexapod walking robots.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…A kinematic model is developed for the proposed design in order to analyze the form of walking pattern, the working space, and the payload 21) . Kinematic Analysis helps to determine the motion capabilities of the robot along with its workspace and the area required for its operation 22) . Literature have shown that there are a number of leg types currently working for hexapod walking robots.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…At discrete positions, KSOM is capable of approximating the inverse kinematics that translate from Cartesian coordinates to the joint space. To guarantee global stability, the inverse kinematic relationship over the entire workspace can be learned using the KSOM-based learning method [29].…”
Section: Position Control Using Ksommentioning
confidence: 99%
“…Neha and shuhaib [13], [14] has done the kinematic analysis and also planned the motion of the fingers such that ,The general solution of joint velocity was interpreted using the generalised inverse of the jacobian matrix; however, this work is accomplished using the pseudo-inverse of the jacobian matrix. E.Neha et al [15] proposed the redundancy resolution schema that was applied to four finger tendon actuated robotic hand and observed that schema can solve redundancies of any robotic hand. Our proposed method provides a generalized framework for generating different gaits by varying the body trajectory parameters.…”
Section: Introductionmentioning
confidence: 99%